An experimental investigation of control parameters in five-axis hybrid parallel kinematic machine in milling of aluminium 6061-T3. (1st August 2019) - Suryam, L.V.; Balakrishna, B.
Surface roughness is an important factor in predicting performance of any machining operation. The experiment has been performed in milling a V-shaped pocket on aluminium 6061-T3 by Exechon parallel kinematic machine using carbide tool. Three different segmented surfaces are selected on V-block and the effect of control parameters were investigated over it. In this research, Taguchi method is used to identify the optimal combination of spindle speed, feed, and depth of cut. To analyse the effect of the control parameters for fine surface finish, Taguchi L9 orthogonal array, signal-to-noise (S/N) ratio and analysis of variance (ANOVA) are employed. Control parameters such as high spindle speed, low feed rate and low depth of cut plays a decisive role in the result of surface roughness. Also, the obtained results from PKM were compared to that of CNC machining, and the surface topologies were examined under optical and scanning electron microscope.